In-situ positive electrode-electrolyte interphase construction enables stable Ah-level Zn-MnO2 batteries - Guojun Lai; Zequan Zhao; Hao Zhang; Xueting Hu; Bingan Lu; Shuquan Liang; Jiang Zhou (Nature Communications)
Abstract Engineering the formulation of an Mn-based positive electrode is a viable strategy for producing an efficient aqueous zinc-ion battery. However, Mn dissolution and the byproducts result in capacity fading, thus limiting its electrochemical performances. To solve the undesirable issues, the concept of in-situ forming the positive electrode/electrolyte interface on the commercial MnO2 is designed, with the help of introducing the Dioctyl Phthalate into the ZS-based electrolyte (2 M ZnSO4 + 0.2 M MnSO4), designated as ZS-DOP electrolyte. An advanced three-dimensional chemical and imaging analysis on a model material reveals the dynamic formation of positive electrode/electrolyte interface. The formed organic interface effectively suppresses the corrosion of the electrolytes with its hydrophobicity, and adjusts the pH value according to Le Chatelier’s Principle to inhibit the production of by-products. Specifically, the pouch cell assembled with the ZS-DOP electrolyte attains a reversible capacity of ~2.5 Ah and powers the unmanned aerial vehicle. Furthermore, photovoltaic energy storage applications deliver a stable capacity of 0.5 Ah and realize the power supply for mobile phones and other electronic devices. Our results facilitate the development of in-situ surface protection on the positive electrode in aqueous zinc-ion battery, providing insights into its practical application.